New Social Movements (A Case Study of Aksi Kamisan in Jakarta) - Atmojo, Bambang Tri; Safara, Yumalaksmi Anggi (Faculty of Social Science, Universitas Negeri Semarang, 2021)
The severe human rights violation cases in the past that have not been resolved by the government trigger the victims and their families to fight for their rights in various ways. The state ignores the lawsuit conveyed by the victims and their families. Therefore, they unite their power to fight collectively through silent protest, namely Aksi Kamisan. Aksi Kamisan has been over 14 years old and this action consistently prosecutes the government to resolve the vicious human rights violations cases. This research aims to find: (1) the background of Aksi Kamisan, (2) the strategy of Aksi Kamisan in reaching its goal, (3) the strategy of Aksi Kamisan in maintaining the movement solidarity. This research used the qualitative method. The research site was in Jakarta, precisely in front of Istana Negara (State Palace). The data were taken from interviews with the initiators and young activists of Aksi Kamisan. The collecting data techniques were performed through interviews, observation, and documentation. This research applied interactive data analysis as the technique of data analysis. Analysis of the data begins with collecting, reducing, presenting, and concluding the data. This research finds out that the background of Aksi Kamisan is due to the struggle of human rights victims and their families that have not been resolved over time. On the other hand, they have grown old. Therefore, all the victims and families initiate to unite their struggle to strengthen their power. The movement strategy used by Aksi Kamisan is doing advocacy with several steps, namely litigation, non-litigation, campaign, and public education. The movement solidarity maintenance is carried out by lifting up the contextual issues or taking an issue from afar to be themed for Aksi Kamisan and its reflection. Another way to keep the solidarity is inviting the other groups outside the activists circle to be involved in helping the struggle of Aksi Kamisan, retreat, the leader’s role, the public engagement, and the regeneration of Aksi Kamisan activists.